The Macroeconomic Effects of Public Debt: An Empirical Analysis of Evidence from Canada - Bahr, Charles; Shan, Lee Hui; Lam, Alfred (Journal of Accounting, Business and Finance Research, 2020)
Public debt refers to the amount of money which a particular country owes to the lenders either inside the country or outside the country. The lenders might be the individuals, businesses or even governments of the other countries. It might also be called as national debt or sovereign debt. Several types are associated with public debt such as domestic debt, external debt and the total debt. Public debt has critical relations with different macroeconomic factors such as economic growth, price levels and exchange rate. In this context, the current study has been conducted with the motive to explore the impact casted by public domestic debt, public external debt and total debt on the macroeconomic factors i.e. economic growth and general price level. As the study has been conducted in the context of Canada, therefore the researcher collected secondary and time series data for Canada. The collected data comprised the time of 28 years. The data regarding the variables of the study was analyzed by using different techniques and tools so that the objective of the study can be fulfilled. The results obtained from the analysis provide information that PDD has negative impact on the economic growth and positive impact on price level in short run as well. In addition, the impact of PED and TD on economic growth is positive only for shorter run and in longer run, this result is not applicable. However, the impact of PED and TD on price levels is too ambiguous to draw any conclusion.